2021
DOI: 10.3390/microorganisms9040692
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana Genes Associated with Cucumber mosaic virus Virulence and Their Link to Virus Seed Transmission

Abstract: Virulence, the effect of pathogen infection on progeny production, is a major determinant of host and pathogen fitness as it affects host fecundity and pathogen transmission. In plant–virus interactions, ample evidence indicates that virulence is genetically controlled by both partners. However, the host genetic determinants are poorly understood. Through a genome-wide association study (GWAS) of 154 Arabidopsis thaliana genotypes infected by Cucumber mosaic virus (CMV), we identified eight host genes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 95 publications
0
21
0
Order By: Relevance
“…However, when genetic markers were selected regarding the LD or tested with statistical models such as MLMM, single significant markers remained good QTL candidates. In that respect, Montes et al (2021), who used FarmCPU to map A. thaliana resistance to CMV, detected eight QTLs, all supported by just one SNP.…”
Section: Other Models That Are More Tailored To Virus Phenotype Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when genetic markers were selected regarding the LD or tested with statistical models such as MLMM, single significant markers remained good QTL candidates. In that respect, Montes et al (2021), who used FarmCPU to map A. thaliana resistance to CMV, detected eight QTLs, all supported by just one SNP.…”
Section: Other Models That Are More Tailored To Virus Phenotype Distributionsmentioning
confidence: 99%
“…ELISA and reverse transcription quantitative PCR (RT-qPCR) can produce both qualitative and quantitative data, but quantitative data are more expensive and time consuming than qualitative ones. Four plant-virus GWAS used quantitative ELISA and three plant-virus GWAS used (RT)-qPCR to measure the Cucumber mosaic virus (CMV) and the Sugarcane yellow leaf virus accumulations in an A. thaliana and a sugarcane diversity panel, respectively [39,65]. Virus accumulation calculated by ELISA or (RT)-qPCR as phenotypic trait gave high heritabilities of between 0.5 and 0.75.…”
Section: Thus Delayed Growth Caused By Viral Infection Was Used By Tamisier Et Al (2020) To Map Pepper Tolerance To the Potato Virus Y (Pmentioning
confidence: 99%
“…Also, in barley and pea, it has been shown that seed transmission of Barley stripe mosaic virus (BSMV) and Pea seed-borne mosaic virus (PSbMV), respectively, is controlled by a few unidentified loci of quantitative effect [ 21 ]. In Arabidopsis, genome-wide association studies have identified genes related to plant response to stresses, embryogenesis, and cell wall metabolism (involved in virus within-host movement) as associated with Cucumber mosaic virus (CMV) seed transmission [ 25 ]. These in silico analyses need to be experimentally validated, but functions of the identified genes agree with predictions above.…”
Section: What Is Known About the Molecular Basis Of Seed Transmission?mentioning
confidence: 99%
“…Rubio et al used TuMV and 317 lines grown under field conditions [11], while Butković et al also used TuMV but 450 lines kept in laboratory conditions [12]. Montes et al [13] and by Liu et al [14] used 156 and . CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%